Arterial Calcifications in Patients with Liver Cirrhosis Are Linked to Hepatic Deficiency of Pyrophosphate Production Restored by Liver Transplantation - Audrey Laurain; Isabelle Rubera; Micheline Razzouk-Cadet; Stéphanie Bonnafous; Miguel Albuquerque; Valérie Paradis; Stéphanie Patouraux; Christophe Duranton; Olivier Lesaux; Georges Lefthériotis; Albert Tran; Rodolphe Anty; et al. (Biomedicines, 2022)
Liver fibrosis is associated with arterial calcification (AC). Since the liver is a source of inorganic pyrophosphate (PPi), an anti-calcifying compound, we investigated the relationship between plasma PPi ([PPi]pl), liver fibrosis, liver function, AC, and the hepatic expression of genes regulating PPi homeostasis. To that aim, we compared [PPi]pl before liver transplantation (LT) and 3 months after LT. We also assessed the expression of four key regulators of PPi in liver tissues and established correlations between AC, and scores of liver fibrosis and liver failure in these patients. LT candidates with various liver diseases were included. AC scores were assessed in coronary arteries, abdominal aorta, and aortic valves. Liver fibrosis was evaluated on liver biopsies and from non-invasive tests (FIB-4 and APRI scores). Liver functions were assessed by measuring serum albumin, ALBI, MELD, and Pugh–Child scores. An enzymatic assay was used to dose [PPi]pl. A group of patients without liver alterations from a previous cohort provided a control group. Gene expression assays were performed with mRNA extracted from liver biopsies and compared between LT recipients and the control individuals. [PPi]pl negatively correlated with APRI (r = −0.57, p = 0.001, n = 29) and FIB-4 (r = −0.47, p = 0.006, n = 29) but not with interstitial fibrosis index from liver biopsies (r = 0.07, p = 0.40, n = 16). Serum albumin positively correlated with [PPi]pl (r = 0.71; p < 0.0001, n = 20). ALBI, MELD, and Pugh–Child scores correlated negatively with [PPi]pl (r = −0.60, p = 0.0005; r = −0.56, p = 0.002; r = −0.41, p = 0.02, respectively, with n = 20). Liver fibrosis assessed on liver biopsies by FIB-4 and by APRI positively correlated with coronary AC (r = 0.51, p = 0.02, n = 16; r = 0.58, p = 0.009, n = 20; r = 0.41, p = 0.04, n = 20, respectively) and with abdominal aorta AC (r = 0.50, p = 0.02, n = 16; r = 0.67, p = 0.002, n = 20; r = 0.61, p = 0.04, n = 20, respectively). FIB-4 also positively correlated with aortic valve calcification (r = 0.40, p = 0.046, n = 20). The key regulator genes of PPi production in liver were lower in patients undergoing liver transplantation as compared to controls. Three months after surgery, serum albumin levels were restored to physiological levels (40 [37–44] vs. 35 [30–40], p = 0.009) and [PPi]pl was normalized (1.40 [1.07–1.86] vs. 0.68 [0.53–0.80] µmol/L, p = 0.0005, n = 12). Liver failure and/or fibrosis correlated with AC in several arterial beds and were associated with low plasma PPi and dysregulation of key proteins involved in PPi homeostasis. Liver transplantation normalized these parameters.